2013
DOI: 10.1017/s0266467413000801
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal transplant experiment suggests host specificity of the mistletoe Agelanthus natalitius in South Africa

Abstract: Abstract:We surveyed the community composition of trees that host the mistletoe Agelanthus natalitius (Loranthaceae) at two sites (Highover and Mtontwane) in South Africa. We recorded a total of 1464 trees (Acacia karroo and A. caffra) hosting 1202 mistletoes in the 64 surveyed plots (20 × 50 m). There were almost four times as many A. karroo as A. caffra at Highover and three times as many A. karroo as A. caffra at Mtontwane. There was no significant difference in prevalence (percentage of infected trees) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…While our results are in agreement with previous studies (e.g. Yan 1993a, b;Fadini 2011), they contrast with others that emphasize a larger role of dispersal patterns as compared to plant compatibility in shaping mistletoe abundance (Roxburgh & Nicolson 2005;Glatzel & Geils 2008;Okubamichael, Griffiths & Ward 2014). Our results also point out that dispersal is important, but in ways that reflect the intricacies of plant-frugivore interactions (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While our results are in agreement with previous studies (e.g. Yan 1993a, b;Fadini 2011), they contrast with others that emphasize a larger role of dispersal patterns as compared to plant compatibility in shaping mistletoe abundance (Roxburgh & Nicolson 2005;Glatzel & Geils 2008;Okubamichael, Griffiths & Ward 2014). Our results also point out that dispersal is important, but in ways that reflect the intricacies of plant-frugivore interactions (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…plant suitability) and to quantify establishment and growth rates of mistletoe among experimental plants (Yan ; Roxburgh & Nicolson ; Messias et al . ; Okubamichael, Griffiths & Ward ; Luo et al . ), we planted seeds of D. caribaeus on branches of selected tree species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clay et al (1985) found that development of haustorial disks of Phoradendron tomentosum seedlings was significantly greater when experimental host and source host species were the same, rather than different, species. Okubamichael et al (2014) also obtained a similar result demonstrating that hypocotyls of Agelanthus natalitius seedlings grew longer within their own source hosts. Dodder ( Cuscuta pentagona ), an aerial parasite, but not a mistletoe, also uses volatile chemicals released by the host to sense the location of the hosts and to cue haustorium development on preferred host species (Runyon et al 2006).…”
Section: Host Abundance and Compatibilitymentioning
confidence: 53%
“…The species popularly known as mistletoes are hemiparasitic plants that grow on tree branches or host shrubs, establishing a connection (via haustorium) with the xylem, in order to get water and nutrients (Okubamichael et al, 2014). In Portuguese, they are called ervas-depassarinho (bird's herb grass) due the dispersion of their seeds, since their fruits feed different species of birds which, when defecating, take the seeds to long distances (Cazzeta and Galletti, 2007).…”
Section: Introductionmentioning
confidence: 99%